Chest-X-ray-based scoring, total leukocyte count, and neutrophil-to-lymphocyte ratio to predict in-hospital mortality in COVID-19 patients: a retrospective study - N., Arvind M.; Patil, Nishant; G., Naveen K. (International Journal of Advances in Medicine, 2022)
Background: The objective of this study was to assess the demographical characteristic, laboratory and radiological findings associated with COVID-19 mortality in hospitalized patients and also to co-relate neutrophil-to-lymphocyte ratio (NLR) and chest x-ray (CXR) score with severity of the disease. Methods: This is a retrospective study done in Bowring and Lady Curzon hospital between the period of May 2021 to July 2021. 100 patients who were tested positive for SARS-CoV2 with RT-PCR were taken for the study after fulfilling the inclusion criteria. On day 1 of admission, routine blood investigations including CBC with differential count and chest X ray is taken. From the above said data, NLR and CXR score is calculated and a comparison is made to determine severity and in-hospital mortality between mild, moderate and severe COVID pneumonia patients. This study is being carried out after obtaining institutional ethical committee approval clearance. All analysis were performed using SPSS software version 10. Results: The sample size studied was 100. The mean age of patients was 28.3 in mild, 49.9 in moderate and 62.6 in severe COVID patients. Among these 67% were males and 33% were females. It was noted that, leukocytosis (mean-13245), neutrophilia (mean-83.05%), lymphocytopenia (mean-10.45%) and chest X-ray score (mean-4.98) was seen among severe group with p value being significant. Conclusions: TLC, NLR and CXR score were significantly different between severe and non-severe patients, so assessment of these simple parameters may help identify high risk COVID-19 patients at an early stage in a resource limited setting from the data retrieved from our hospital, NLR and CXR Score showed an acceptable efficiency to separate COVID-19 patients among severe and non-severe patients with a significant p value thereby helping in triaging the patients and need for early ICU needs.